102k views
0 votes
-4y - 20 +19= -y + 17

2. Solve for y

i posted the same question but they didn’t tell me how they got it so could someone show me how they got the answer pleaseee

1 Answer

5 votes

Answer:

y= -6

Explanation:

-4y - 20 + 19 = -y + 17 *add y on the right to get rid of -y

+y +y then add it to -4y

-3y - 20 + 19 = 17 *add 20 to the left to get rid of -20

+20 +20 then add it to 17

-3y + 19 = 37 *subtract 19 from the left to get rid of 19

-19 -19 then subtrcat 19 from 37 as well

-3y = 18 *now we want to divide both sides by -3 to

-3 -3 get y by it's self

y = -6 *no we're left with y = -6 :D

- im sorry if this doesn't make sense x(

User Ninthpower
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.